PREDIKSI PENJUALAN BUKET BUNGA DENGAN METODE EXPONENTIAL SMOOTHING - Astuti, Vivi Rizki Indri; Zuliarso, Eri (Information Technology and Telematics, 2018)
Abstract- Sales is an activity that aims to find, influence and give instructions to buyers in order to adjust their needs with the products offered and enter into agreements regarding prices that are beneficial to both parties. A common problem faced by Bouquet of Flowers is how to predict or forecast the sale of interest in the future based on previous sales data. The method used to predict sales in this case is the single exponential smoothing method. The single exponential smoothing method will try to get sales forecasts and can be seen in the picture of sales fluctuations. In this method forecasting is done by repeating calculations continuously using the latest data, each of the latest data is given a greater weight.The final result of this study is the prediction of Bouquet Flower sales with exponential smoothing method with a value of α = 0.5 obtained MSE value of 220.408.848.886.482, the value of α = 0.7 obtained MSE values ​​of 245.896.287.781.153, the value of α = 0.8 obtained MSE value of 262,328,991,357,180 and the value of α = 0.9 obtained an MSE value of 281,555,575,487,970. Of the three values ​​α = 0.5, α = 0.7, α = 0.8 and α = 0.9, the smallest MSE value is α = 0.5 so the prediction of Buket Bunga sales with exponential smoothing method uses the value α = 0 , 5